Health Risk Assessment of Potentially Toxic Elements Contamination of Commonly Consumed Fruits in Bahir Dar Town, Northwest Ethiopia - Biset Asrade Mekonnen; Muluabay Getie Yizengaw; Haile Kassahun; Gebremariam Ketema (International Journal of Food Science)
Background. Excess accumulation of potentially toxic elements in frequently consumed fruits is a serious threat to human health. The aim of this study was to determine the levels of cadmium (Cd), chromium (Cr), copper (Cu), and lead (Pb) and to estimate the noncarcinogenic and carcinogenic health risks associated with their daily intake in commonly consumed fruits in Bahir Dar town, northwest Ethiopia. Methods. Three types of fruits (mango, banana, and orange) were collected using a simple random sampling method from open markets in Bahir Dar town. Wet digestion was used, and the concentration of potentially toxic elements was analyzed in the edible portion of the fruits. The average daily intake (ADI), hazard quotient (HQ), hazard index (HI), and target cancer risk (TCR) were estimated to assess the human health risks posed by the intake of those potentially toxic elements from the consumption of the studied fruits. Results. The concentrations of Cr and Cu were lower than the maximum limit of normal values in mango, banana, and orange. However, the Pb and Cd concentrations (mg kg-1) in mango were 0.576 and 1.771, respectively, which exceeded the FAO/WHO recommended permissible limits of 0.3 mg kg-1 and 0.2 mg kg-1, respectively. The ADI of potentially toxic elements was found to be lower than the maximum permitted tolerable daily intake in the studied fruits, and the HI values (mgday-1 kg-1) of all studied potentially toxic elements were lower than one in banana and orange, except mango (3.69). The TCR values for Pb, Cd, and Cr in banana and orange were 7.16×10−4 and 7.15×10−4, respectively, which exceeded the recommended threshold risk limit (>1×10−4), but in mango (1.71×10−3), the level was above the moderate risk limit (>1×10−3). However, the TCR value in all the studied fruits was above the recommended safe limit (ILCR<1×10−6) set by the United States Environmental Protection Agency (US-EPA). Conclusion. The study revealed that the consumption of mango fruit in the studied areas may pose noncarcinogenic and carcinogenic adverse health effects.